(untitled) (Pedagogy of Higher and Secondary Education, 2004)
It was considered the insertion of various educational forms in out-of-school activities based on the principle of unity of pedagogical management with the development of pupil’s activity, self-dependence, and initiative as one of pedagogical conditions used in spiritual senior pupils’ education of youth musical subculture.